Profil dan Frekuensi Belanja Online Generasi Z di Platfrom E-Commerce pada Aplikasi Shopee - Maharani Br Saragih; M. Irwan Padli Nasution (Universitas 45 Surabaya, 2025)
This study aims to analyze the demographic profile, shopping behavior characteristics, and online shopping frequency of Generation Z in Indonesia, with a focus on the use of the Shopee e-commerce platform. As digital natives, Gen Z has a high level of access to technology, which shapes active consumption patterns. They represent an important market segment in the e-commerce industry because their shopping habits are strongly influenced by digital technology. This study employs a descriptive quantitative method by distributing questionnaires to Gen Z respondents who are active Shopee users. The collected data are analyzed using descriptive statistics to describe user profiles, shopping intensity, and the factors influencing their purchasing decisions. The results show that Gen Z has a relatively high shopping frequency, influenced by various factors such as promotions, ease of use of the application, and stimulating features such as Shopee Live. In addition, reviews, product ratings, and recommendations from social media and influencers also have a significant impact on their purchasing decisions. These findings provide important insights for e-commerce practitioners to optimize more personalized and effective marketing strategies in order to attract attention and meet the shopping needs of Gen Z on digital platforms.